Sistem Pendukung Keputusan Pemilihan Perusahaan Ekspedisi Menggunakan Metode Analytic Network Process - Jackri Hendrik; Feriani Astuti Tarigan (Bulletin of Computer Science Research, 2023)
CV. Wahana Gemilang Trans is a company that often uses transportation services from other shipping companies. The selection of a shipping company that involves many factors can be confusing. There are times when the shipping costs offered are quite affordable so that they can reduce shipping costs, but goods are often late, or claims for damaged goods take a long time. This problem can be solved by building a Decision Support System (DSS) application. The research used the Analytic Network Process (ANP) method. Variable data or assessment criteria for shipping companies taken from CV. Wahana Gemilang Trans, namely claims for damaged goods, shipping costs, delivery delay times, service for tracking orders and response speed. The first step is to make comparisons between criteria. Then this method looks for the weights for each criterion and ensures that the comparison of the criteria is consistent. After that, the value of each shipping company is calculated. The end result of the ANP method is the ranking of shipping companies, starting from the highest value to the lowest value. Applications can be used to choose the right shipping company in minimizing delivery delays, namely by analyzing the dependence between criteria, so that the best criteria are selected using the ANP method.